Interplanetary shocks and foreshocks observed by STEREO during 2007–2010. Issue 2 (19th February 2016) - Blanco‐Cano, X.; Kajdič, P.; Aguilar‐Rodríguez, E.; Russell, C. T.; Jian, L. K.; Luhmann, J. G.
Abstract: Interplanetary shocks in the heliosphere modify the solar wind through which they pass. In particular, shocks play an important role in particle acceleration. During the extended solar minimum (2007–2010) STEREO observed 65 forward shocks driven by stream interactions (SI), with magnetosonic Mach numbers M ms  ≈ 1.1–4.0 and shock normal angles θ B N  ~ 20–87°. We analyze the waves associated with these shocks and find that the region upstream can be permeated by whistler waves ( f  ~ 1 Hz) and/or ultra low frequency (ULF) waves ( f  ~ 10 −2 –10 −1  Hz). While whistlers appear to be generated at the shock, the origin of ULF waves is most probably associated with local kinetic ion instabilities. We find that when the Mach number ( M ms ) is low and the shock is quasi‐perpendicular ( θ B N  > 45°) whistler waves remain close to the shock. As M ms increases, the shock profile changes and can develop a foot and overshoot associated with ion reflection and gyration. Whistler precursors can be superposed on the foot region, so that some quasi‐perpendicular shocks have characteristics of both subcritical and supercritical shocks. When the shock is quasi‐parallel ( θ B N  < 45°) a large foreshock with suprathermal ions and waves can form. Upstream, there are whistler trains at higher frequencies whose characteristics can be slightly modified probably by reflected and/or leaked ions and by almost circularly polarized waves at lower frequencies that may be locally generated by ion instabilities. In contrast with planetary bow shocks, most of the upstream waves studied here are mainly transverse and no steepening occurs. Some quasi‐perpendicular shocks (45° <  θ B N  < 60°) are preceded by ULF waves and ion foreshocks. Fluctuations downstream of quasi‐parallel shocks tend to have larger amplitudes than waves in the sheath of quasi‐perpendicular shocks. We compare SI‐driven shock properties with those of shocks generated by interplanetary coronal mass ejections (ICMEs). During the same years, STEREO observed 20 ICME‐driven shocks with M ms  ≈ 1.2–4.0 and θ B N  ~ 38–85°. We find that shocks driven by ICMEs tend to have larger proton foreshocks (dr ~ 0.1 AU) than shocks driven by stream interactions (dr ≤ 0.05 AU). This difference of ion foreshock size should be linked to shock age: ICME‐driven shocks form at shorter distances to the Sun and therefore can energize particles for longer times as they propagate to 1 AU, while stream interaction shocks form closer to Earth's orbit and have been accelerating ions for a shorter interval of time. Key Points: Characteristics of waves in foreshock ahead of interplanetary shocks Study of shock profiles depending on their geometry Foreshock extensions